Signature of circulating microRNAs as potential biomarkers in vulnerable coronary artery disease. - Jingyi Ren; Jing Zhang; Ning Xu; Guanping Han; Qiang Geng; Junxian Song; Sufang Li; Jianqing Zhao; Hong Chen (PLoS ONE, 2013)
AIMS: MicroRNAs (miRNAs) play important roles in the pathogenesis of cardiovascular diseases. Circulating miRNAs were recently identified as biomarkers for various physiological and pathological conditions. In this study, we aimed to identify the circulating miRNA fingerprint of vulnerable coronary artery disease (CAD) and explore its potential as a novel biomarker for this disease. METHODS AND RESULTS: The Taqman low-density miRNA array and coexpression network analyses were used to identify distinct miRNA expression profiles in the plasma of patients with typical unstable angina (UA) and angiographically documented CAD (UA group, n = 13) compared to individuals with non-cardiac chest pain (control group, n = 13). Significantly elevated expression levels of miR-106b/25 cluster, miR-17/92a cluster, miR-21/590-5p family, miR-126*, and miR-451 were observed in UA patients compared to controls. These findings were validated by real-time PCR in another 45 UA patients, 31 stable angina patients, and 37 controls. In addition, miR-106b, miR-25, miR-92a, miR-21, miR-590-5p, miR-126* and miR-451 were upregulated in microparticles (MPs) isolated from the plasma of UA patients (n = 5) compared to controls (n = 5). Using flow cytometry and immunolabeling, we further found that Annexin V(+) MPs were increased in the plasma samples of UA patients compared to controls, and the majority of the increased MPs in plasma were shown to be Annexin V(+) CD31(+) MPs. The findings suggest that Annexin V(+) CD31(+) MPs may contribute to the elevated expression of the selected miRNAs in the circulation of patients with vulnerable CAD. CONCLUSION: The circulating miRNA signature, consisting of the miR-106b/25 cluster, miR-17/92a cluster, miR-21/590-5p family, miR-126* and miR-451, may be used as a novel biomarker for vulnerable CAD. TRIAL REGISTRATION: Chinese Clinical Trial Register, ChiCTR-OCH-12002349.